Kandungan Logam Berat Timbal (Pb) dan Tembaga (Cu) pada Karang Pocillopora damicornis di Perairan Taman Nasional Karimunjawa - Faiz, Muhamad Ziaul; Sabdono, Agus; Ambariyanto, Ambariyanto (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Human activities in the Karimunjawa National Park increase water pollution, including heavy metals such as lead (Pb) and copper (Cu). The existence of heavy metals in sea waters can not be degraded, but it can be absorbed and accumulated in the body of organisms, including coral, Pocillopora damicornis. Given the existence of coral P. damicornis as sessile organism which are able to absorb lead (Pb) and copper (Cu) from the water, therefore, it is necessary to conduct research on heavy metals content in the coral. The purpose of this study was to determine the content of heavy metals lead (Pb) and copper (Cu) on the coral P. damicornis taken from several locations around the Karimunjawa National Park. The results of the study showed that heavy metals content in the water was not detected. While the highest Pb and Cu were found in the coral collected from Burung Island that was equal to 0.00405 ppm and 0.01121 ppm, respectively. The lowest Pb substance were found in the coral collected from Kemojan canal i.e. 0.00143 ppm. Sample collected from Indonoor, Kemojan canal and Karimunjawa port did not contain Cu substance. Based on Pb and Cu data contained in the coral and water samples Minister of Environment Decree No.51st, 2004, it could be concluded that the conditions of Karimunjawa National Park was still in the stage of no contamination.